A just world on a safe planet: A Lancet Planetary Health–Earth Commission report on Earth-System boundaries, translations, and transformations - Gupta, Joyeeta; Lade, Steven J.; Winkelmann, Ricarda; Kılkış, Şiir; Inoue, Cristina Y.A.; Hurlbert, Margot; Huang, Lei; Hoff, Holger; Green, Pamela A.; Crona, Beatrice; Bulkeley, Harriet; Broadgate, Wendy J.; et al. (Elsevier, 2024)
The health of the planet and its people are at risk. The deterioration of the global commons—ie, the natural systems that support life on Earth—is exacerbating energy, food, and water insecurity, and increasing the risk of disease, disaster, displacement, and conflict. In this Commission, we quantify safe and just Earth-system boundaries (ESBs) and assess minimum access to natural resources required for human dignity and to enable escape from poverty. Collectively, these describe a safe and just corridor that is essential to ensuring sustainable and resilient human and planetary health and thriving in the Anthropocene. We then discuss the need for translation of ESBs across scales to inform science-based targets for action by key actors (and the challenges in doing so), and conclude by identifying the system transformations necessary to bring about a safe and just future.